World congress on medical physics and biomedical engineering May 26-31, 2012, Beijing, China - Long, Mian (IFMBE Proceedings, 2013)
The congress's unique structure represents the two dimensions of technology and medicine: 13 themes on science and medical technologies intersect with five challenging main topics of medicine to create a maximum of synergy and integration of aspects on research, development and application. Each of the congress themes was chaired by two leading experts. The themes address specific topics of medicine and technology that provide multiple and excellent opportunities for exchanges.